ADVOKASI GERAKAN PEREMPUAN EROPA DALAM INSTITUSIONALISASI NORMA KESETARAAN GENDER INTERNASIONAL - Dewi Setiyaningsih (Universitas Muhammadiyah Yogyakarta, 2016)
This research illuminates the struggle of women’s movement in putting the gender equality norm into international politics. From the constructivism paradigm, gender equality norm can be seen as something that created by agent. Using the concept of Life Cycle of Norm by Martha Finnemore, this research discovered that the global gender equality norm’s growth through three stages, its emergence process, cascade process and internalization process. This research focuses on the cascade process, where the gender equality norm became institutionalized. It examines the strategy of women’s movement and its obstacles, in affecting the global agenda setting until it emerged global gender equality norm, it marked by the forming of global gender instrument and its effect on domestic policy